Assessing the Professional Preparedness of English Studies Graduates in Morocco: An Alumni Perspective on the Applied Linguistics Track - Ayoub Bahnasse; Meriem Harrizi; Ayoub Loutfi; Said Zaidoune (Journal of English Language Teaching and Linguistics, 2023)
This paper evaluates the effectiveness of the sixth semester of applied linguistics in the English studies track in preparing students for the job market in Morocco. A questionnaire survey was conducted with alumni of the program to assess the extent to which the program facilitated their employment, career advancement, and fulfillment of professional expectations. The results revealed that involving alumni in the development and renewal of the track is crucial. However, a significant number of participants expressed dissatisfaction with the current curriculum, citing difficulties in professional integration. The findings suggest that incorporating practical training and offering more elective courses could better equip students with the necessary skills and knowledge to succeed in the job market. Based on these findings, the paper concludes with recommendations for enhancing the English studies track, including the routine evaluation of academic programs to align with market needs and promote curriculum changes and innovations. It is believed that these recommendations will ultimately improve students' professional integration in the job market.